Outlook on satellite communications network architecture for 6G - Xiaowen WU; Zhenfeng JIAO; Xiang LING; Bing LIU; Lidong ZHU; Lei HAN (Dianxin kexue)
The future satellite communications network architecture for 6G was analyzed, studied and imagined.Through introducing the current trends of satellite and ground communications integration, with the current research results of 6G network architecture with its vision and requirements, the technical characteristics of 6G network architecture were summarized.The key role of artificial intelligent (AI) in 6G network was deeply explored based on the research and application analysis of AI in the field of communications.Therefore, the idea of AI enabled 6G satellite communications network overall architecture, RAN architecture, core network architecture were proposed, also with step-by-step evolution and implementation.Finally, the enhanced robust mechanism of 6G satellite communication network based on block-chain was also discussed.